Método de las relaciones casuales para la planificación del desarrollo sostenible. Aplicación en pulpochoque - Solano, David (2007)
The barrires to a society´s sustainable development are typically the result of many problem-cause interactions, which may be of an economic, socio-cultural, technological or political nature. In order to fi nd proper solutions, it is important to differentiate between problem-cause and problemresult relations; only with this method will it be possible to ensure sustainability. The Cause Relation Method is a tool that identifi es causes and consequences starting with the relations between problems. This method may be used to generate participatory decisions that foster the integrated action of a community to address the constraints to its development.